PENGUNGKAPAN TANGGUNGJAWAB SOSIAL DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN DAN UKURAN PERUSAHAAN (Fokus Ekonomi, 2011)
The aim of this is to examine some determinants the disclosure of social responsibility (CSR) companies and their impact on financial performance and company size. This study uses secondary data from the 2006-2009 annual reports of public companies listed in Bursa Efek Indonesia (BEI) and data from the IndonesianSustainability Reporting Award (ISRA) in the period 2007-2008. The sample in this study of 47 companies consisting of receivers and that did not receive Indonesian Sustainability Reporting Award (ISRA) in the same industry. In thefirst hypothesis using logistic regression, shows that firmsize andROA have an influence on the disclosure of corporate social responsibility (CSR), while the ROE has no effect on CSR. In the second  and  third  hypotheses using  differenttest  shows that firmsize that receives Indonesian Sustainability Reporting Award (ISRA) higher than those not receiving Indonesian Sustainability Reporting Award (ISRA). As for financial performance  asmeasured  by  ROA  and ROE no difference  betweenthe recipientand who do not receive the Indonesian Sustainability Reporting Award (ISRA).